ChemInform Abstract: New Developments in Spin Labels for Pulsed Dipolar EPR. Issue 26 (June 2016) - Fielding, Alistair J.; Concilio, Maria Grazia; Heaven, Graham; Hollas, Michael A.
Abstract: Review: 152 refs.